Biologically inspired mobile agent-based sensor network (BIMAS) - Ponnusamy, V. (Inderscience Enterprises Ltd., 2014)
Sensor nodes deployed in a large topology require autonomous capabilities and scalability since frequent replacement of the nodes is almost impossible. These sensors should be self-healing and energy efficient. Biologically inspired algorithms offer a new paradigm in providing solutions to problems found within the wireless sensor networks (WSNs). In this paper, bee nectar harvesting (analogous to data harvesting from sensor nodes) and flower pollination (analogous to energy harvesting in sensor nodes) are proposed with detailed mapping. Simulation was conducted to evaluate the proposed mechanism and a prototype was developed to show the feasibility of mobile agent de-ployment and energy provisioning. The research outcome is a biologically inspired mobile agent-based system (BIMAS) that provides a novel self-healing (bee pollination analogy for energy efficiency) protocol, leading to a longer WSNs lifetime. BIMAS is aimed for delay tolerant applications and where sensor node replacement is almost impossible. Copyright Â© 2014 Inderscience Enterprises Ltd.